Arts and Culture Learning at UNP Pembangunan Labor Middle School - Alfi Nusrotin; Harisnal Hadi (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This research aims to understand and explain Arts and Culture Learning at the UNP Laboratory Development Middle School. The research method used is qualitative with a descriptive approach. Researchers act as the main instrument, supported by tools such as stationery, cameras and cellphones. Data collection was carried out through literature study, observation, interviews and documentation. Data analysis includes steps such as collection, classification, clarification, analysis, description, and conclusion. The research results show that at the learning planning stage, not all aspects follow the teaching module guidelines according to independent curriculum standards, so that the implementation of learning is not optimal. The learning methods and strategies applied by teachers are not in line with learning achievements and the flow of learning objectives which are monitored through formative assessments in the independent curriculum. The mismatch between the material in the teaching module and what is delivered as well as the lack of teacher involvement in students' practical piano playing training produces negative impacts. Furthermore, teachers do not carry out enrichment or remedial work based on the practical value of playing musical instruments, so that summative assessments cannot function as an evaluation tool to assess the achievement of learning outcomes in practicing playing musical instruments by students.